Serum Cytokines Correlated with The Disease Severity of Generalized Pustular Psoriasis - Masaaki Yamamoto (Disease Markers, 2013)
To characterize serum biomarkers reflecting the severity of generalized pustular psoriasis (GPP), we measured multiple cytokine/chemokine levels in 39 serum samples from 6 cases with GPP during the course of the disease. Serum levels of IL-4, IL-8, CXCL1 and CCL3 were positively correlated with the severity scores of GPP, white blood cell counts and serum C-reactive protein levels. Serum levels of IL-1β, IL-1ra, IL-6, IL-10, IL-12p70, IL-18, IL-22, IFN-γ and VEGF showed strong positive correlations (r > 0.4, p < 0.01) with all those 3 clinical markers. Of those, IL-10 and IL-22 were significantly decreased after treatment in parallel with the GPP score and therefore those two serum cytokines might be useful to evaluate the efficacy of treatment for GPP.